Hf layer thickness dependence of resistive switching characteristics of Ti/Hf/HfO2/Au resistive random access memory device. (17th May 2018) - Nakajima, Ryo; Azuma, Atsushi; Yoshida, Hayato; Shimizu, Tomohiro; Ito, Takeshi; Shingubara, Shoso
Abstract: Resistive random access memory (ReRAM) devices with a HfO2 dielectric layer have been studied extensively owing to the good reproducibility of their SET/RESET switching properties. Furthermore, it was reported that a thin Hf layer next to a HfO2 layer stabilized switching properties because of the oxygen scavenging effect. In this work, we studied the Hf thickness dependence of the resistance switching characteristics of a Ti/Hf/HfO2 /Au ReRAM device. It is found that the optimum Hf thickness is approximately 10 nm to obtain good reproducibility of SET/RESET voltages with a small RESET current. However, when the Hf thickness was very small (∼2 nm), the device failed after the first RESET process owing to the very large RESET current. In the case of a very thick Hf layer (∼20 nm), RESET did not occur owing to the formation of a leaky dielectric layer. We observed the occurrence of multiple resistance states in the RESET process of the device with a Hf thickness of 10 nm by increasing the RESET voltage stepwise.